Anatomic variations of the hepatic arterial irrigation in a Mexican population: contrast enhanced computer tomography evaluation: a cross-sectional study - Castillo-Martinez, Daniel Benito; Palacios-Rivera, Doris Michelle; Boy-Serratos, Jorge (International Journal of Research in Medical Sciences, 2022)
Background: Knowledge and mastery of the anatomical variability of the hepatic arteries are essential for surgical disciplines and, given their complexity and importance over time, they have been extensively studied and described. Methods: A retrospective, cross-sectional, analytical study was carried out in which contrast-enhanced computer tomography (CT) studies carried out between January 2021 and December 2021 at the North Central PEMEX hospital were analyzed. A total of 207 contrast-enhanced CT scans were analyzed, and Statistical analysis was performed with the statistical software IBM® SPSS© Statistics. Results: Uflacker type I CT was found in 90.8%, the Michel class I hepatic arterial irrigation in 70.5%, and the origin of CA was documented in the right hepatic arteries (RHA) in 90.3%. Multiple cystic artery (Cas) were identified in 1% and Moynihan's hump in 0.5%. The mean length of the common hepatic artery (CHA) was 53 millimeters. Conclusions: The tomographic study of the anatomical variants of hepatic irrigation is an accessible and non-invasive tool. The nomenclature described in the present work allows a precise and straightforward understanding of clinical-surgical utility.